Do saber sábio ao saber ensinado: indicativos sobre a transposição didática do conceito evolução biológica - Servat, Alexandre (2014)
The scientific production undertaken in multiple strands of science is faced with a significant problem that is the selection, adaptation or reformulation of the knowledge produced by scientists in order to make it accessible to teaching. The concept of biological evolution was selected for this study because it is considered a unifying concept and structuring of biological knowledge. By understanding the process of didactic transposition of the concept of biological evolution substantially tangent social, cultural and epistemological instances, we adopt the KVP model (Knowledge (K), values (V) and Social Practices (P) of didactic transposition) to guide the analysis data. In this context, the general objective of the research is to investigate indicative of the didactic transposition of the concept of biological evolution, since the levels of scientific production to the processes of teaching and learning process of basic education. To do so, the implementation process has led us to investigate the concept of biological evolution present in the last five years in two Brazilian scientific journals that discuss epistemological aspects of biology; clarify the research on biological evolution in textbooks of secondary education and research on conceptions of biological evolution of biology teachers (Higher and Secondary Education) as well as those on conceptions of biological evolution of Basic Education students - always by bank analysis of theses and dissertations of capes. Furthermore, we analyzed the National Curriculum Guidelines for courses in Biological Sciences, in order to verify that introduce the concept of biological evolution as a unifying element of biology, and the role that the concept of biological evolution assumes the National Curricular Parameters for High School to thus identify similarities and differences of scientific knowledge about biological evolution and knowledge built in the context of the classroom. The work consisted in a survey of state of the art, conducted by analysis of PCNEM, the Curriculum Guidelines for courses in biological sciences, dissertation and thesis database Capes and scientific journals that discuss epistemological aspects of biology. The results of our research show that the academic production of knowledge Wise (TDE), referring to biological evolution, presents both discussions regarding the construction of the synthetic theory of evolution as elements of pre-synthesis and post-synthesis. As for more contemporary discussions, proposing the expansion of the synthetic theory of evolution, it has notes about evo-devo, epigenetics, plasticity and phenotypic xi accommodation, niche construction, multilevel selection and exaptations. Recent discussions suggest overcoming the genecentrista vision and uniqueness of natural selection as an explanatory foundation for the evolutionary process. However, research indicated that there is a delay period of relatively large didactic transposition between the expanded discussions of concepts such as evolution, epigenetics and gene and inserting these concepts in school curricula and textbooks. In additio